In silico structural homology modelling of EST073 motif coding protein of tea Camellia sinensis (L) - K. H. T. Karunarathna; N. H. K. S. Senathilake; K. M. Mewan; O. V. D. S. J. Weerasena; S. A. C. N. Perera (Journal of Genetic Engineering and Biotechnology, 2020)
Abstract Background Tea (Camellia sinensis (L). O. Kuntze) is known as the oldest, mild stimulating caffeine containing non-alcoholic beverage. One of the major threats in south Asian tea industry is the blister blight leaf disease (BB), caused by the fungus Exobasidium vexans Masse. SSR DNA marker EST SSR 073 is used as a molecular marker to tag blister blight disease resistance trait of tea. The amino acid sequences were derived from cDNA sequences related to EST SSR 073 of BB susceptible (TRI 2023) and BB resistant (TRI 2043) cultivars. An attempt has been made to understand the structural characteristics and variations of EST SSR 073 locus that may reveal the factors influencing the BB resistance of tea with multiple bioinformatics tools such as ORF finder, ExPasy ProtParam tools, modeler V 9.17, Rampage server, UCSF-Chimera, and HADDOCK docking server. Results The primary, secondary, and tertiary structures of EST SSR 073 coding protein were analyzed using the amino acid sequences of both BB resistant TRI 2043 and BB susceptible TRI 2023 tea cultivars. The coding amino acid sequences of both the cultivars were homologous to photosystem I subunit protein (PsaD I) of Pisum sativum. The predicted 3D structures of proteins were validated and considered as an acceptable overall stereochemical quality. The BB resistant protein showed CT repeat extension and did not involve in topology of the PsaD I subunit. The C terminal truncation of BB resistance caused the formation of hydrogen bonds interacting with PsaD I and other subunits of photosystem I in the modeled three-dimensional protein structure. Conclusions Camellia sinensis EST 073 SSR motif coding protein was identified as the PsaD I subunit of photosystem I. The exact mechanism of PsaD I conferring the resistance for blister blight in tea needs to be further investigated.